Association between the uric acid to high density lipoprotein cholesterol ratio and alanine transaminase in Chinese short stature children and adolescents: A cross-sectional study - Li, Guangxin; Zhao, Qianqian; Zhang, Xinran; Ban, Bo; Zhang, Mei (Frontiers in Nutrition, 2023)
This research aimed to investigate the relationship between the uric acid to high-density lipoprotein cholesterol ratio (UHR) and alanine aminotransferase (ALT) in children and adolescents with short stature.